2019
DOI: 10.1128/aem.01615-19
|View full text |Cite
|
Sign up to set email alerts
|

Role of BGS13 in the Secretory Mechanism of Pichia pastoris

Abstract: The methylotrophic yeast Pichia pastoris has been utilized for heterologous protein expression for over 30 years. Because P. pastoris secretes few of its own proteins, the exported recombinant protein is the major polypeptide in the extracellular medium, making purification relatively easy. Unfortunately, some recombinant proteins intended for secretion are retained within the cell. A mutant strain isolated in our laboratory, containing a disruption of the BGS13 gene, displayed elevated levels of secretion for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…For the BGS targets no mutation frequency was calculated, as only very few colonies were sequenced. The frameshifts in the targets BGS5 , BGS7 , and BGS12 , as well as the in-frame deletion in BGS13 , however, confirm the results of Cereghino et al who reported insertions of integration cassettes in those open reading frames previously, while still reporting an intact reading frame for BGS13 [ 51 , 52 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…For the BGS targets no mutation frequency was calculated, as only very few colonies were sequenced. The frameshifts in the targets BGS5 , BGS7 , and BGS12 , as well as the in-frame deletion in BGS13 , however, confirm the results of Cereghino et al who reported insertions of integration cassettes in those open reading frames previously, while still reporting an intact reading frame for BGS13 [ 51 , 52 ].…”
Section: Discussionsupporting
confidence: 85%
“…In total, 20 genes of interest were identified, of which 5 were chosen for a more detailed analysis of CRISPR/Cas9 on- and off-target effects, based on preliminary results and position in the genome ( Table 1 ). Cereghino et al have identified targets whose disruption might have positive effects on the secretion of the reporter protein beta galactosidase [ 51 , 52 ]. We have chosen to include 4 of those genes as targets and named them BGS5 , BGS7 , BGS12 and BGS13 in accordance with Cereghino et al ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to S. cerevisiae, YPS1 gene mutants of P. pastoris grew normally in the presence of CFW or CR (Guan et al, 2012;Naranjo et al, 2019) phenotype of yps1 strains is not affected in the presence of two cell wall-disrupting reagents (Kang et al, 1998;Yao et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A BLAST search revealed that Bgs13 is the K. phaffii homolog of S. cerevisiae Pkc1. The role of Bgs13/Pkc1 has been further investigated by analyzing strains expressing the truncated variant of this essential protein ( Naranjo et al, 2019 ). The mutant strain showed an abnormal localization of the Bgs13 variant and its cell wall suffered from inherent structural problems, which most probably promoted improved protein secretion.…”
Section: The Cell Wallmentioning
confidence: 99%